2021
DOI: 10.1007/s11128-021-03211-z
|View full text |Cite
|
Sign up to set email alerts
|

Sharing quantum steering among multiple Alices and Bobs via a two-qubit Werner state

Abstract: Quantum steering, a type of quantum correlation with unique asymmetry, has important applications in asymmetric quantum information tasks. We consider a new quantum steering scenario in which one half of a two-qubit Werner state is sequentially measured by multiple Alices and the other half by multiple Bobs. We find that the maximum number of Alices who can share steering with a single Bob increases from 2 to 5 when the number of measurement settings N increases from 2 to 16. Furthermore, we find a counterintu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Until now, all researches aimed at improving the efficiency of EPR steering has been restricted to local measurements [25][26][27][28][29] , In the case of local measurements, each observer measures the qubit in the hand. Mathematically, each observer's measurement results can be obtained by measuring his or her respective reduced density matrices.…”
Section: Activationmentioning
confidence: 99%
“…Until now, all researches aimed at improving the efficiency of EPR steering has been restricted to local measurements [25][26][27][28][29] , In the case of local measurements, each observer measures the qubit in the hand. Mathematically, each observer's measurement results can be obtained by measuring his or her respective reduced density matrices.…”
Section: Activationmentioning
confidence: 99%
“…The Hamiltonian (37) indicates that the superradiant-phase Hamiltonian can act as two driving super-mode oscillators.…”
Section: Epr Steering Between Photons and Atoms In The Superadiant Phasementioning
confidence: 99%
“…They found that by adjusting the measurement sharpness, the former party can extract sufficient nonlocality and maintain enough entanglement, enabling sequential parties to share Bell nonlocality simultaneously [16]. Since then, unsharp measurement has been widely applied in sharing quantum correlations [17], such as standard Bell nonlocality [18][19][20][21][22][23], network nonlocality [24][25][26][27][28][29], steering [30][31][32][33][34][35][36][37][38][39], entanglement [40][41][42][43][44], coherence [45,46], and contextuality [47,48]. Moreover, it has been observed that these shared quantum correlations are closely connected to numerous quantum information tasks, including quantum random access code [49][50][51][52], randomness certification [53][54][55], self-testing [56,57] and revealing 'hidden' nonlocality [58].…”
Section: Introductionmentioning
confidence: 99%